Perceived Human Rights in Van Merkez, Eastern Turkey. Issue 4 (4th July 2017) - Hemmerechts, Kenneth; Smets, Kevin; Timmerman, Christiane
Abstract: The Kurdish population in Turkey and its human rights situation have been a major issue in Turkey's foreign and domestic politics. There is a need for large-scale empirical evidence on perceptions of human rights or how people judge their own life situation and obstacles to greater empowerment and freedom of choice in the predominantly Kurdish eastern part of Turkey. Providing such empirical input, this study offers insight into the perceived human rights of people living in Van Merkez, an area that has been shaped by the Kurdish conflict. The data are part of the EUMAGINE project on human rights and migration-related perceptions, and consist of survey questions about human rights conditions among a representative sample of 500 respondents aged 18‒39. The results show that the differences in perceptions between Kurds and Turks are partially explained by the life satisfaction, perceptions of corruption and safety of respondents. The largest part is explained by the perception of language discrimination by the government.